An Exploratory Study on Status of Homestays from Lamjung - Ghimire, Maya Nath; Neupane, Dasarath (Nepal Journal of Multidisciplinary Research, 2022)
This is a preliminary assessment on the situation of homestays in Lamjung, Nepal. This study is a comparison of international, national, and local home stays in Nepal's Lamjung district. The core topic of the study was an investigation of the guest's desired and existing facilities, biodiversity (agriculture, forest, and wild life), conservation role, income, and interest in stays. In-depth interviews were used in a qualitative study. The study was carried out in three home stay locations: SAARC village home stay Ghalegaun, national home stay Kaulepani Gaunsahar, and local home stay Rainaskot in Nepal's Lamjung district. The guest desired a variety of facilities such as an attached bathroom with hot and cold water, traditional food and cultural programs and attire. There are a neat and clean atmosphere with beautiful Himalaya views. It is suggested to visit these places at least once.